PENDAPATAN ASLI DAERAH, BELANJA PEMERINTAH, DAN INDEKS PEMBANGUNAN MANUSIA DALAM MEMPENGARUHI PDRB KABUPATEN SUMBAWA - Sulandari, S; Sucihati, Roos Nana (Jurnal Ekonomi & Bisnis, 2025)
This study aims to determine the effect of Local Revenue, Government Expenditure, and Human Development Index on GRDP of Sumbawa District. The type of this study was associative study with quantitative approach. The type of data used was quantitative obtained from secondary sources using documentation techniques. The data used in this study are data on Local Revenue, Government Expenditure, and Human Development Index, and GRDP of Sumbawa District for 2014-2023. Data were analyzed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination testing (). The result of this study showed that the Local Revenue, Government Expenditure, and Human Development Index had a positive and significant effect on GRDP of Sumbawa District for 2014-2023, either partially or simultaneously. The ability of the Local Revenue, Government Expenditure, and Human Development Index variables to effected on GRDP of Sumbawa District was 94.3%, while the remaining of 5.7% was effected by other variables outside this research model, such as population, workforce, foreign investment and domestic investment.